Digital knowledge repositories: the effectiveness and challenges in Majlis Bandaraya Melaka Bersejarah (MBMB) / Anis Nabeela Azman ... [et al.] - Azman, Anis Nabeela; Wahid, Ezzah Han's; Samsuddin, Nor Hafiza; A'zemim, Nurul Afiqah (2006)
In today's world, all business is persistently required to do some transformation their business process. Digital knowledge repository will help to get better, quickly and more efficiently. It is an online database that systematically captures, organizes, and categorizes knowledge based information. The research target organization is Majlis Bandaraya Bersejarah (MBMB). The research addressed the following research objectives: a) to investigate the effectiveness execution of digital knowledge repository and b) to explore the challenges of implementing digital knowledge repository in (MBMB). By using quantitative research, a survey questionnaire was used as the instrument and Simple Random Techniques as the Sampling Techniques. The researcher is able to collect 87.6 percent of the distributed questionnaires from the respondents. Findings show that the leveraging of digital knowledge repository in MBMB does exist. Thus, this study proposed changes in technology, top management support, training and awareness to encourage staff to implement the digital knowledge repository in the organization.